2007
DOI: 10.1111/j.1600-0625.2007.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dermatophyte species causing onychomycosis and tinea pedis by MALDI‐TOF mass spectrometry

Abstract: Identification of dermatophytes is currently performed based on morphological criteria and is increasingly supported by genomic sequence comparison. The present study evaluates an alternative based on the analysis of clinical fungal isolates by mass spectrometry. Samples originating from skin and nail were characterized morphologically and by sequencing the internal transcribed spacer 1 (ITS1), ITS2 and the 5.8S rDNA regions of the rDNA clusters. In a blind comparative study, samples were analyzed by matrix as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
0
13

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 23 publications
2
84
0
13
Order By: Relevance
“…Only more recently has this technology been applied directly to unfractionated fungal colonies (10,11,17). Studies examining the application of MADLI-TOF MS specifically for dermatophyte identification are limited (6), and to our knowledge, there have been no published studies to date on the performance of the Bruker Biotyper system (Bruker Daltonics, Billerica, MA) for the identification of dermatophytes.…”
mentioning
confidence: 99%
“…Only more recently has this technology been applied directly to unfractionated fungal colonies (10,11,17). Studies examining the application of MADLI-TOF MS specifically for dermatophyte identification are limited (6), and to our knowledge, there have been no published studies to date on the performance of the Bruker Biotyper system (Bruker Daltonics, Billerica, MA) for the identification of dermatophytes.…”
mentioning
confidence: 99%
“…D ermatophytes in the genera Epidermophyton, Microsporum, and Trichophyton are usually characterized and identified by cultural and morphological characters and physiological tests or, more recently, by sequencing (1). Morphological identification is time-consuming and complex, usually requiring expert mycological knowledge, while sequencing is comparatively expensive and at least 2 to 3 days elapse before sequencing results are available.Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS) is a reliable technique for the identification and typing of microbial pathogens such as bacteria (2-7), yeasts (8-10), and filamentous fungi, including dermatophytes (7,(11)(12)(13)(14)(15)(16)(17). Recent studies confirm that this technique may be very attractive for dermatophyte identification (18-22).…”
mentioning
confidence: 99%
“…Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS) is a reliable technique for the identification and typing of microbial pathogens such as bacteria (2-7), yeasts (8-10), and filamentous fungi, including dermatophytes (7,(11)(12)(13)(14)(15)(16)(17). Recent studies confirm that this technique may be very attractive for dermatophyte identification (18-22).…”
mentioning
confidence: 99%
“…For bacterial identification by MALDI-TOF MS fingerprinting, the spectral profile of the strain of interest is compared to a spectral library of reference strains. Several private databases have been created, including spectral profiles of more than 500 bacterial strains, such as The Spectral Archive And Microbial Identification System (Saramis TM ; AnagnosTec GmbH, Potsdam, Germany) (Erhard et al, 2008) and the Microbelynx bacterial identification system (Waters Corporation, Manchester, UK) (Keys et al, 2004;Dare, 2006). The MALDI Biotyper 2.0 (Bruker Daltonics) search against an ample database of more than 1800 bacterial species and new spectral profiles are being added on a daily basis.…”
Section: Maldi-tof Ms Fingerprinting a Rapid And Reliable Methods Formentioning
confidence: 99%
“…The difficulty in taking the correct amount of biomass complicates to get a homogenous distribution of the sample and matrix. Although, this technique was successfully applied for bacterial species identification (Keys et al, 2004;Erhard et al, 2008), it has been shown that spectra showed more noise and less peak resolution with this fast method, making difficult to obtain reproducible spectral profiles (Böhme et al, 2010b). Another sample preparation technique analyzed cell suspensions that were obtained after harvesting bacterial biomass in a solvent, including one or two washing steps and resuspension of the pellet in the matrix solution (Mazzeo et al, 2006;Vargha et al, 2006).…”
Section: Sample Preparation Protocolmentioning
confidence: 99%